USULAN RANCANGAN MEJA DAN BANGKU KANTIN MENGGUNAKAN PENDEKATANQUALITY FUNCTION DEVELOPMENT DAN ANTHROPOMETRI (STUDI KASUS: UNIVERSITAS ESA UNGGUL) (Jurnal Inovisi (Teknik Industri), 2017)
AbstractThe canteen isone of an important facility to support the success of students in campus life, in addition to a place to enjoy food and drinks, the canteen is also used to do college assignments.The observation shown at the EsaUnggul University canteen, there are several problems with damaged and uncomfortable benches to use.Preliminary research data collection was carried out by interviewing 10 students.Data and information are used for product design purposes through distributing questionnaires to 30 customers / students as respondents. Questionnaire testing with validity and reliability test shows that the questionnaire is valid and reliable. There are 16 important attributes for canteen table design and 15 attributes for stool design. The results of the analysis using the Quality Fuction Deployment to meet consumer needs, it is suggested that the table-chair size be a unit with a capacity of up to 6 people. The dimensions for chairs and tables follow the anthropometric data of the measured respondents. Keywords : Validitas, Reliabilitas, Atribut,Quality Function Deployment, Antropometri AbstrakKantin merupakan fasilitas penting untuk menunjang keberhasilan mahasiswa dalam kehidupan kampus, selain tempat untuk menikmati makanan dan minuman kantin   juga digunakan untuk mengerjakan tugas-tugas kuliah. Hasil pengamatan pada kantin Universitas Esa Unggul, terdapat beberapa masalah bangku yang rusak dan kurang nyaman digunakan. Pengumpulan data penelitian pendahuluan dilakukan dengan wawancara dengan 10 orang mahasiwa. Data dan informasi untuk keperluan perancangan produk melalui penyebaran kuisioner dengan responden sebanyak 30 orang pelanggan/mahasiswa. Pengujian kuisioner dengan uji validitas dan reliabilitas menunjukkan kuisioner valid dan reliabel. Terdapat 16 atribut penting untuk desain meja kantin dan 15 atribut untuk desain bangku. Hasil analisis menggunakan Quality Fuction Deployment untuk memnuhi kebutuhan konsumen diusulkan ukuran meja-kursi menjadi kesatuan dengan kapasitas hingga 6 orang. Dimensi untuk kursi dan meja mengikuti data antropometri dari responden yang diukur. Kata kunci : Validitas, Reliabilitas, Atribut, Quality Function Deployment, Antropometri